Thomas becket: Damnatio Memoriae and the marking of books. Issue 3 (1st October 2020) - Smith, Jeremy J.
ABSTRACT: William Caxton, England's first printer, published the first edition of his English Golden Legend in 1483–4. Caxton's edition, a magnificent folio with many woodcuts, was a translation and conflation of three earlier texts: a twelfth-century Latin cycle of saints' live s and materials appropriate for church feasts, and French and earlier English translations of the same work. But Caxton's version was not only another translation, but also added new material, including extended versions of the life of Thomas Becket, and a narrative relating to the miracles surrounding the translation of his relics to the new shrine. Later, copies of this book were regularly annotated, in a hostile manner, by those readers who looked on Becket as a traitor to his king. In this article, I place Caxton's Golden Legend in its context, and discuss how its subsequent mutilation related to other socio-cultural developments in sixteenth-century England.